Indonesia Employment in 2023: Labor Force Conditions and Policy Developments in the Early Stages of the Demographic Bonus - Muhyiddin, Muhyiddin; Trisnantari, Sita Agung; Amrizal, M. Dio Rhiza; Fauwziyah, Fahimah; Harsiwie, Riesa Istiqamah Putri; Ardhana, Narifha Rizky (Jurnal Ketenagakerjaan, 2024)
In 2023, amidst the complexities of a volatile global economy, Indonesia demonstrated economic resilience, propelled by its dynamic workforce. This abstract synthesizes the intricate interplay between macroeconomic forces and employment trends within Indonesia, drawing from comprehensive data analyses and policy evaluations. The report encapsulates a year marked by economic recovery despite global headwinds such as the Russia-Ukraine conflict, inflation surges, and supply chain interruptions. With a predicted global growth of 3.6% by the IMF, Indonesia's economy experienced fluctuations but maintained a growth trajectory from Q2 2022 to Q2 2023. Labor force data indicates a predominance of the working-age population, signaling potential for sustained productivity and economic fortitude. The demographic composition, skewed towards a younger populace, underpins the vibrant labor market. Employment policies have been responsive to digitalization, globalization, and demographic transitions, focusing on skill development, vocational training, and job safety. Notably, vocational training for SMK graduates was prioritized to match industry requirements. Regulatory advancements aim to balance worker protections with corporate operational efficiency. Amidst COVID-19's lingering impact, policy adaptations were crucial to support workers and businesses, exemplifying Indonesia’s agility in times of crisis. The landscape of employment disputes, predominantly centered around termination, underscores the necessity for robust conflict resolution mechanisms. With 71.15% of industrial disputes tied to terminations, mediation emerged as the preferred dispute resolution strategy. Regional data unveiled disparities in job placements and complaints, spotlighting the need for equitable workforce distribution and grievance redressal mechanisms. The report concludes that Indonesia's labor policies and employment conditions are dynamically evolving, poised to sculpt a robust, inclusive, and sustainable labor market landscape.